Management of exercise-induced bronchoconstriction in athletes - Koya, T.; Ueno, H.; Hasegawa, T.; Arakawa, M.; Kikuchi, T. (The Journal of Allergy and Clinical Immunology, 2020)
Exercise-induced bronchoconstriction (EIB) is a phenomenon observed in asthma but is also seen in healthy individuals and frequently in athletes. High prevalence rates are observed in athletes engaged in endurance sports, winter sports, and swimming. The pathophysiology of EIB is thought to be related to hyperventilation, cold air, and epithelial damage caused by chlorine and fine particles in inspired air. Several diagnostic procedures can be used; however, the diagnosis of EIB based on self-reported symptoms is not reliable and requires an objective examination. The hyperosmolar inhalation test and eucapnic voluntary hyperpnea test, which involve indirect stimulation of the airway, are useful for the diagnosis of EIB. A short-acting ß-agonist is the first choice for prevention of EIB, and an inhaled corticosteroid is essential for patients with asthma. Furthermore, treatment should accommodate antidoping requirements in elite athletes. Tailoring of the therapeutic strategy to the individual case and the prognosis after cessation of athletic activity are issues that should be clarified in the future.